Design, implementation and test of a serious online game for exploring complex relationships of sustainable land management and human well-being. (March 2015) - Schulze, Jule; Martin, Romina; Finger, Alexander; Henzen, Christin; Lindner, Martin; Pietzsch, Katrin; Werntze, Andreas; Zander, Ute; Seppelt, Ralf
Abstract: Land is a limited resource providing various services. Decisions on land use shape the distribution of these life support functions and thus require understanding of complex feedbacks between decisions on land use and human resource appropriation. Due to multiple nonlinear feedbacks between management, productivity, environmental quality, and human well-being, complexity is an inherent property of land systems. We present an educational game, which aims at illustrating options of sustainable land management to the interested public, students and stakeholders. The game provides the opportunity to govern a country by exploring how contrasting dimensions of sustainability (economy, environment and social conditions), can be harmonized regionally, while continuously being threatened by global trade fluctuations. The game was tested by several groups of students from high schools and universities. The feedback shows that the game is a valuable tool in environmental education initiating learning the complexity of feedbacks in land use and resources appropriation. Graphical abstract: Highlights: Land management requires understanding of nonlinear dynamic feedbacks in land systems. LandYOUs, a serious online game, explains various facets of sustainable land management. The player governs a country by means of land use, nature protection and education. The game was tested by several groups of students from high schools and universities. User feedback supports the potential for applications in environmental education.